Pemberdayaan Masyarakat Melalui Peningkatan Sumber Daya Manusia di Desa Sungai Seluang Pasar Kabupaten Barito Kuala - Helmiyah, Fauzatul; Khairussalam, Khairussalam; Hamid, Ismar; Priatna, Myra Pionera Prhameswari; Putra, Ezza Akhnan Maulana; Latifah, Latifah; Maryam, Siti; Faizi, Muhammad Noor; Rahmadani, Ariska (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
The lack of community participation in empowerment programs and the low quality of human resources are the main problems in Sungai Seluang Pasar Village. So that the solution designed by the service team to overcome these problems is to carry out a service program. The service activities designed are based on the community's social routine which includes 3 aspects, namely environmental aspects, educational aspects, and social or community aspects. The implementation of activities applies a community empowerment approach, which includes enabling, empowering and protecting. Activities are carried out systematically from the initial stage to the final stage to achieve targeted outputs and outcomes. The service was carried out in Sungai Seluang Pasar Village, Belawang District, Barito Kuala Regency, on July 16, 2023 to August 21, 2023. The results obtained from this service are the level of community participation in the empowerment program began to increase compared to before and the quality of Human Resources (HR) also began to improve. This can be seen from the strengthening of community awareness of the environment so that they are able to maintain and utilize the environment properly, increase community knowledge, and active involvement of the entire community in every social activity. The community service carried out is able to be one of the solutions to overcome the problems found in Sungai Seluang Pasar Village. With a service program designed based on social routines carried out, the community is able to be empowered and community welfare can increase.